Does attachment style moderate the effect of computer‐mediated versus face‐to‐face conflict discussions?. Issue 4 (9th November 2020) - Pollmann, Monique M. H.; Crockett, Erin E.; Vanden Abeele, Mariek M. P.; Schouten, Alexander P.
Abstract: Successful conflict resolution is important in romantic relationships. With the advent of computer‐mediated communication (CMC), partners can resolve conflict using CMC. But is CMC as effective as face‐to‐face communication for conflict resolution? And does the effectiveness depend on attachment style? We asked 100 romantic couples to discuss a conflict topic and randomly assigned them to do so face‐to‐face or via CMC. Levels of distress, anger, and conflict resolution did not differ between face‐to‐face and CMC discussions. Attachment style did not moderate these findings. A more anxious and a more avoidant attachment style were associated with higher levels of distress and anger. We conclude that there is no indication that resolving conflict face‐to‐face has advantages over resolving conflict via CMC.